Fenomena Pegiat Game pada Kelompok Usia Muda (Studi Fenomenologi pada Game God of War Ragnarok di Pondok Kopi Jakarta Timur) - yogatama, andika yogatama; Ramdhani, Muhammad; Oxcygentri, Oky (Peneliti.net, 2024)
God of War Ragnarok, which was released on November 9, 2022, with the adventure genre, was popular in the East Jakarta area when it was first released. The popularity of this game is interesting to research because according to data from statista.com, games with the adventure genre are less attractive to Indonesian gamers in 2022. This study aims to find out what is the motive for someone to play this game until this game was popular, especially in Pondok Kopi, East Jakarta. This study used qualitative research methods with Alfred Schutz's phenomenological approach. The subjects of this study consisted of five youth age group game activists in Pondok Kopi, East Jakarta. Using interview, conservation, triangulation and documentation methods. The results of this study found that someone's motive for playing God of War Ragnarok is because of media impressions, friend invitations, following trends, nostalgia and wanting to collect the game. There is also a different God of War game experience today when compared to the PlayStation 2 era, starting from changes in graphics and game features to mobile games that are more in demand and more online games that make the lack of togetherness playing games that now feel more individual.